PELATIHAN PENGEMASAN PRODUK SINGPONG DAN NINGPONG DI DESA PANGPONG, KABUPATEN BANGKALAN-MADURA (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The rapid and dynamic development of science and technology and the beginning of the era of globalization that spread throughout the world, make packaging or packaging have a very important role in the commodity or packaged products. This is closely related to the selling value and product image that cannot be separated from the packaging itself. Good packaging must also pay attention to the use of packaging raw materials and packaging design factors that greatly determine the selling power of a packaged product. These factors make packaging more and more noticed by the business community about the products that are circulated.The big market opportunity that is owned by the residents of Pangpong Village, Labang Subdistrict, Bangkalan Madura Regency cannot be maximally achieved, this is due to the lack of innovation in the packaging of cassava and marning products they produce using ordinary packaging plastic, which results in a lack of consumer interest to buy the product. Keywords: training, packaging, packaging training, product packaging, singpong and ningpong